The Source of the Sunnah of the Prophet in Surat Al-Ahzab: (A Fundamentalist Study) (Raparin Journal of Humanities (RJH), 2022)
It appeared from time to time some people make the Holy Qur’an the only source for enacting rulings;  They intend by this to strip the Prophetic Sunnah from its source and authenticity, and they base their claim in that on suspicions that make people believe that the Qur’an is the one who ordered us to make it the only source of legislation.  It contains the provisions in total, and the Prophetic Sunnah is the one that took care of clarifying its details, and explaining its summaries.  And in the Qur’an itself there are many verses that prove that the Sunnah is one of the sources of legislation. Among these verses are verses in Surat Al-Ahzab.